1992
DOI: 10.1103/physreva.45.4438
|View full text |Cite
|
Sign up to set email alerts
|

Alternative basis functions forL2calculations on the molecular continuum. II. Integrals with higher-order functions

Abstract: By differentiation of the expressions for the basic s-type integrals previously presented, analytic expressions are here derived for integrals, relevant for quantum-chemistry calculations, involving oscillating Hermite Gaussian functions (OHGF's) and many-center Hermite Gaussian functions (HGF's) of any order. The OHGF is the product of a HGF and a radial trigonometric factor cos(kr), and has been proposed for describing the continuum orbitals in L calculations on molecules. The resulting expressions are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…These basis functions combine the oscillating character of a trigonometric factor [cos(kr)] with the "transferability" of the HGF's and therefore represent a convenient basis set for such calculations. The quality of the description of the continuum orbital can be considered comparable with that already obtained by the STOCOS's [9] (as explicitly shown in a following paper [14]), with the advantage of not being limited to a particular class of molecules. Such a description is therefore [7] much superior to that offered by spherically averaged plane waves [12] or pure Gaussian sets [13], which latter can represent only a limited number of radial nodes because of redundancy problems that can be easily avoided using a set of OHGF's.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These basis functions combine the oscillating character of a trigonometric factor [cos(kr)] with the "transferability" of the HGF's and therefore represent a convenient basis set for such calculations. The quality of the description of the continuum orbital can be considered comparable with that already obtained by the STOCOS's [9] (as explicitly shown in a following paper [14]), with the advantage of not being limited to a particular class of molecules. Such a description is therefore [7] much superior to that offered by spherically averaged plane waves [12] or pure Gaussian sets [13], which latter can represent only a limited number of radial nodes because of redundancy problems that can be easily avoided using a set of OHGF's.…”
Section: Discussionsupporting
confidence: 54%
“…However, numerical tests have shown that a basis set of OHGF's and many-center HGF's can be considered competitive with the ones currently employed even by the direct application of the expressions here presented. In a following paper [14] we will derive the formulas for the integ rais involving higher-order functions; however, we note that the s-type functions considered here can be directly utilized as such in molecular calculations by adopting a "lobe-Gaussianfunction" approach [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we will now discuss those properties of \documentclass{article}\pagestyle{empty}\begin{document}$\mathcal{Y}^{m}_{\ell}(\nabla)$\end{document} that are needed for the derivation of addition theorems for B functions. Other properties as well as numerous applications—mainly in the context of multicenter integrals—are described in the literature 6, 19, 29, 55, 57, 93, 105–135.…”
Section: The Translation Operator In Spherical Formmentioning
confidence: 99%
“…In this section, those properties of the spherical tensor gradient operator 𝒴 italiclitalicm(∇) are reviewed that are needed for the derivation of addition theorems. Other properties as well as numerous applications—mainly in the context of molecular multicenter integrals—can be found in the literature 43, 55, 65, 74, 84, 86–112.…”
Section: Properties Of the Spherical Tensor Gradient Operatormentioning
confidence: 99%